Evidence of the middle Miocene paratethys transgression from Jurkowice-Budy site (SE Holy Cross Mountains, Poland - Reutt, Olga; Westphal, Piotr (Acta Geographica Lodziensia, 2021)
Identifying ancient shores may provide valuable information concerning sea-level fluctuations and environmental changes, since they serve as a reliable marker of palaeoshorelines. This paper deals with deposits that display features of a nearshore zone. In the Jurkowice-Budy quarry (southern slopes of the Holy Cross Mountains) a sequence of clastic sediments and littoral structures linked to the transgression of the Paratethys Sea in the middle Miocene has been recognised. The discovery of bio-erosional assemblages (borings of lithophags) in Devonian limestone boulders helped to determine the littoral nature of the examined deposits and to layout a palaeocliff wall. The samples of sandy sediments were analysed by sieving procedure and interpreted using statistical parameters calculated by graphic and moment methods. Moreover, morphometric analysis of gravels and analysis of mineralogical composition under binocular microscope were performed. The results showed well-developed beach assemblages composed of pebbles, coarse-to-medium sands and silty sands derived from eroded Cambrian strata (sand-stones) located to the north of the study site.